MEMORIES OF THE CAXIAS' “RODA DE CAPOEIRA” (Fiep Bulletin - online, 2015)
This paper aims at describing the memories about the Caxias “Roda” de capoeira as they are presented in the testimonials of former founders and participants. In order to do so, we have carried an ethnographic research during the year of 2003 to understand who the social agents share their memories of one of the most traditional and important “rodas” de capoeira in Brazil. The profile of the current participant in the “Roda” de Caxias was mapped through the replies to fifty questionnaires applied among its frequenters. The appearance of this “roda de capoeira” in the 70s was characterized as an alternative model, which to a certain extent, created conditions for the co-existence, not always pacific, among participants and representatives of the Angola and Regional “capoeira schools”.
Keywords: Capoeira; Roda de Caxias; Popular Culture; Ethnography.